Self-study of language and literacy teacher education practices : culturally and linguistically diverse contexts - Sharkey, Judy; Peercy, Megan Madigan (Bingley, U.K. : Emerald Publishing Limited, 2018)
This volume explores how Self-Study in Teacher Education Practices (S-STEP) contribute to teacher education in culturally and linguistically diverse communities and contexts. The chapters reflect the scholarly inquiry of teacher educators dedicated to investigating and opening to public scrutiny their efforts to improve their practice, while recognizing the impacts of such efforts on their students and teacher education overall. The common thread in these S-STEP inquiries is the explicit attention to the ways in which culture, language, and race interact and affect teaching and learning. Central to this are the ways in which S-STEP studies address two pressing but interrelated issues in teacher education research: the need for greater attention to teacher educator development and pedagogies overall, and the challenge of preparing teachers for increasingly diverse, mobile, and plurilingual schools and communities. The book will be a valuable resource for teacher educators, particularly second language teacher education scholars and those new to S-STEP methods.
Prelims -- Enhancing teacher education for an inclusive pluralistic world: a shared commitment across multiple landscapes -- Teacher educator professional development in culturally and linguistically diverse contexts: a lifelong process -- Pedagogical practices and policies related to linguistic diversity and language development -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Teachers -- Training of; Language teachers -- Training of; Reading teachers -- Training of; English teachers -- Training of; Literacy; Language and languages -- Study and teaching; Education -- Teaching Methods & Materials -- General; Teaching skills & techniques